An individual approach to monitoring locomotive training load in English Premier League academy soccer players: Commentary - Drust, B. (International Journal of Sports Science & Coaching, 2018)
Research that examines the activity profiles of players in team sports (specifically football) has traditionally used parameters to describe activity that are based around the velocity of movement. This approach is probably based on the theoretical assumption that such classifications can help potentially provide information on both the energy system contribution and the overall energy expenditure associated with the activity(s). The classification of activities in the majority of the research is based on arbitrary thresholds that have unclear origins. Most commonly, these thresholds seem to be more of a product of commercial companies who specialise in providing tracking data for practical athlete monitoring than any scientifically agreed criteria.